Fatigue behaviour of Ti-6Al-4V alloy under combined low and high cycle and ultrasonic loading. (1st January 2014) - Cho, In-Sik; Park, Jinil; Jeon, Yongho
The importance of the fatigue behaviour of Ti-6Al-4V alloys aerospace parts at low and high cycles has gained strength in last decades due to their long service life. In this study, an ultrasonic nanocrystalline surface modification (UNSM treatment was performed on a Ti-6Al-4V alloy in order to extend the fatigue behaviour using a hydraulic and ultrasonic fatigue testing (UFT systems. The fatigue enhancement mechanism of Ti-6Al-4V alloy was discussed on the residual stress and S-N behaviour with X-ray diffraction results. High-cycle fatigue behaviour of Ti-6Al-4V alloy was studied up to 10 7 –10 9 using a piezoelectric ultrasonic fatigue tester operating at 20 kHz. The high-cycle fatigue results showed that the UNSM-treated specimen had better performances. Failure in the Ti-6Al-4V alloy was observed around the gigacycle regime with the fractures being found to initiate from the surface. The fracture surfaces exhibit brittle characteristics containing river patterns and cleavage facets, as well as striations.